Silence, masculinity, and collapse: A theoretical-analytical analysis of men's mental health in contemporary Brazil (Research, Society and Development, 2026)
Male suicide overmortality is a persistent public health problem in Brazil, showing a consistent epidemiological pattern over the last few decades. This study aims to analyze the psychosocial determinants associated with male mental health, articulating national epidemiological evidence, international literature on suicidal behavior, and theoretical frameworks of masculinities. The methodology adopted consisted of a qualitative theoretical-analytical essay, based on a narrative review of the scientific literature and documentary analysis of secondary data from the Mortality Information System (SIM) and official epidemiological bulletins from the Ministry of Health, complemented by reports from the World Health Organization. The results indicate a growing trend in male suicide mortality rates, with a continued predominance of men among registered deaths, as well as heterogeneous territorial distribution and a significant association with mental disorders, especially depression, anxiety, and substance use. It was evidenced that cultural norms associated with hegemonic masculinity, socioeconomic inequalities, and institutional barriers to care contribute to maintaining the pattern of male vulnerability. It is concluded that male suicide in Brazil should be understood as a multi-causal phenomenon that articulates clinical, cultural, and structural dimensions. Reducing preventable deaths depends on incorporating men's mental health as a strategic axis of public policies, with the strengthening of primary care, socio-emotional education, interventions in the workplace, and communication campaigns sensitive to gender specificities.